Substitusion of Mackerel (Rastrelliger sp) on Nugget Products as Emergency Food - Addiniawati, Nur; Srimiati, Mia; Agestika, Lina (Sarana Ilmu Indonesia (salnesia), 2024)
In emergencies, ensuring proper nutrition for toddlers is crucial, including the availability of specialized food products such as mackerel-based nuggets. This study aim to evaluate the impact of mackerel substitution on organoleptic characteristics, proximate composition, fatty acid profile, and Vitamin D content in nuggets as emergency food. The research employed an experimental approach using a completely randomized design (CRD) with three treatment groups and one control: F0 (0%), F1 (40%), F2 (50%), and F3 (60%). Organoleptic data were analyzed using the Kruskal-Wallis, and the Mann-Whitney test to determine statistical significance. Meanwhile, proximate composition (protein, fat, carbohydrates, moisture content, and ash content), fatty acid profile, and vitamin D levels were examined using an independent t-test. Findings from the hedonic test revealed that F3 (60%) was the most preferred formula. This formula exhibited a slightly brownish color, a strong aroma, a somewhat soft texture, and an intense flavor. Proximate analysis showed that F3 contained 16,18 g of carbohydrates, 2,88 g of fat, 21,65 g of protein, 2,24 g of ash, and 57,05 g of moisture. Additionally, its fatty acid composition included 0,0864% DHA, 0,0079% EPA, 0,1005% omega-3 fatty acids, 0,3083% omega-6 fatty acids, 1,255% omega-9 fatty acids, and 0,0096% linolenic acid. The vitamin D content in this formula was recorded at 1,13 mcg. The study results indicated significant differences between the control and the selected formula in terms of proximate composition, fatty acid profile, and Vitamin D levels. Therefore, incorporating mackerel into nugget production can enhance the product's organoleptic characteristics